Exploring the Causes of Inter-Religious Marriages in Bangladesh: A Socio-Cultural Analysis - Md. Nazrul Islam (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to analyze the socio-cultural factors behind the increasing practice of interfaith marriage in Bangladesh, with an emphasis on the dynamics of value shifts, identity construction, and marriage practices in the broader context of social change. Theoretical framework: This study uses a socio-anthropological perspective by referring to the theories of social change, secularization, and cultural integration to explain how the transformation of modern values and identities affects the practice of interfaith marriage. Literature review: Most previous studies have highlighted interfaith marriage from a legal, moral, and theological perspective. This study expands the discussion by emphasizing the influence of urbanization, education, media, local cultural traditions (Baul and Sufi), and individual autonomy as driving factors for interfaith interaction and marriage. Methods: Using a qualitative approach through in-depth interviews, questionnaires, and document analysis of seven informants (interfaith couples, parents, students, and scholars). The data was analyzed by thematic analysis to find the main patterns in respondents' experiences and views. Results: The study found that interfaith marriage in Bangladesh is influenced by urbanization, secular values, weakening religious authority, access to higher education, and media influence. The emphasis on individual autonomy as well as legal support through the Special Marriage Act of 1872 was also an important factor, plus inclusive cultural traditions such as Baul and Sufi. However, this dynamic creates tensions with Islamic law, family norms, and religious values. Implications: Implications of these findings include the need for legal reforms that balance individual rights and social harmony, the improvement of social literacy and interfaith understanding for education, and the role of religious leaders in fostering interfaith dialogue and awareness programs. Novelty: The authenticity of the research lies in its focus on the socio-cultural realities of couples and families, not solely on legal or moral aspects. The novelty of this study lies in the integration of urbanization factors, local cultural traditions, and family dynamics to explain the shifting boundaries of interfaith marriage in Bangladesh.